(untitled) (TEST Ticontre. Theory Text Translation, 2014)
Si presenta la prima traduzione in italiano del saggio A Literature without Qualities di John McGahern, uno dei più importanti scrittori irlandesi del XX secolo, contenuto nella raccolta postuma del 2009 Love of the World curata da Stanley van der Ziel. This article presents an italian translation of A Literature without Qualities by John McGahern, one of the most valuable writers that Ireland bore in the XX century. This essay can be found in the posthumous collection Love of the World, edited in 2009 by Stanley van der Ziel.